2016
DOI: 10.1016/j.ajo.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Panretinal Photocoagulation Versus Ranibizumab for Proliferative Diabetic Retinopathy: Patient-Centered Outcomes From a Randomized Clinical Trial

Abstract: Purpose Compare patient-centered outcomes in patients with proliferative diabetic retinopathy (PDR) treated with ranibizumab versus panretinal photocoagulation (PRP). Design Randomized clinical trial. Methods Setting: Multicenter (55 US sites). Patient Population: 216 adults with one study eye out of 305 adults (excluding participants with two study eyes since each eye received a different treatment) with PDR, visual acuity 20/320 or better, no history of PRP. Intervention: Ranibizumab (0.5-mg/0.05mL) vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…Cells are naturally provided with antioxidant mechanisms protecting them from ROS activity in order to keep a balanced internal milieu. However, in critical situations such as oxidative stress, these mechanisms are not sufficient and fail to keep the balance [9]. Thus, exogenous antioxidants are suggested to have a protective and/or curative role against ROSinduced cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Cells are naturally provided with antioxidant mechanisms protecting them from ROS activity in order to keep a balanced internal milieu. However, in critical situations such as oxidative stress, these mechanisms are not sufficient and fail to keep the balance [9]. Thus, exogenous antioxidants are suggested to have a protective and/or curative role against ROSinduced cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the follow-up durations of these studies were no more than 48 weeks, reminding us that researches on long-term outcomes are necessary. No difference was identified between the two treatment regimens for PDR in most of the patient-centered outcomes (Beaulieu et al, 2016). The unique 5-year study reported the similar outcome of visual acuity in most eyes of PRP and anti-VEGF monotherapy (Gross et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Another point to consider is that recent prevalent use of anti‐VEGF and anti‐inflammatory drugs might be changing the definition of diabetic retinopathy that requires treatment. Emerging data show that anti‐VEGF and glucocorticoid therapies can reverse diabetic retinopathy, and even work better than panretinal and focal macular photocoagulation. Thus, screening algorithms and intervals might be better focused on more subclinical stages and entirely different in the future.…”
Section: Screening Schedule and The Corresponding Probability Of Progmentioning
confidence: 99%